Corrosion Inhibitors, Principles and Recent Applications - Aliofkhazraei, Mahmood (IntechOpen, 2018)
To protect metals or alloys from corrosion, some methods can be used such as isolating the structure from the aggressive media or compensating the loss of electrons from the corroded structure. The use of corrosion inhibitors may include organic and inorganic compounds that adsorb on the metallic structure to isolate it from its surrounding media to decrease oxidation-reduction processes. This book collects new developments about corrosion inhibitors and their recent applications.